2006
DOI: 10.1111/j.1574-6968.2005.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a genotyping scheme forCoxiella burnetii

Abstract: Coxiella burnetii is the causative agent of Q fever. The bacterium is highly infectious and is classified as a category B biological weapon. The tools of molecular biology are of utmost importance in a rapid and unambiguous identification of C. burnetii in naturally occurring Q fever outbreaks, or in cases of a deliberate release of the infectious agent. In this work, development of a multiple locus variable number tandem repeats (VNTR) analysis (MLVA) for the characterization of C. burnetii is described. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
76
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 28 publications
0
76
0
2
Order By: Relevance
“…Because of a correlation between plasmid type and disease presentation (human acute or chronic), Samuel et al (93) first proposed that C. burnetii isolates have distinct pathogenetic potential, an hypothesis later buttressed by a restriction fragment length polymorphism study of 32 isolates that showed disease associations between six defined genomic groups (I to VI) (51). More recently, three studies using PCR-restriction fragment length polymorphism examination of the isocitrate dehydrogenase gene (76), multiple-locus variable-number tandem-repeat analysis (104), and multispacer sequence typing (37) have again revealed relationships between C. burnetii's genome composition and disease outcome. However, it is also clear that existing host conditions, such as heart valve abnormalities in the context of cytokine-mediated immunosuppression, are critical cofactors in the evolution of chronic endocarditis (49,87).…”
mentioning
confidence: 99%
“…Because of a correlation between plasmid type and disease presentation (human acute or chronic), Samuel et al (93) first proposed that C. burnetii isolates have distinct pathogenetic potential, an hypothesis later buttressed by a restriction fragment length polymorphism study of 32 isolates that showed disease associations between six defined genomic groups (I to VI) (51). More recently, three studies using PCR-restriction fragment length polymorphism examination of the isocitrate dehydrogenase gene (76), multiple-locus variable-number tandem-repeat analysis (104), and multispacer sequence typing (37) have again revealed relationships between C. burnetii's genome composition and disease outcome. However, it is also clear that existing host conditions, such as heart valve abnormalities in the context of cytokine-mediated immunosuppression, are critical cofactors in the evolution of chronic endocarditis (49,87).…”
mentioning
confidence: 99%
“…Jager et al used restriction fragment length polymorphism (RFLP) to differentiate 80 C. burnetii isolates and reproduced distinguishable patterns for reference isolates in groups I, IV, V, and VI (23). More recently, multiple-locus variable nucleotide tandem repeat analyses (49) have validated these groupings. Infrequent-restriction-site PCR of 14 livestock and tick isolates resulted in six groups; subsequent multiple-locus variable-number tandem repeat analysis typing of 42 isolates revealed 36 genotypes (2).…”
mentioning
confidence: 99%
“…In this study we assessed the feasibility of using multiple-locus variable-number tandem-repeat (VNTR) analysis (MLVA) as a novel approach to the genetic fingerprinting of A. phagocytophilum. MLVA has previously been shown to offer very good discriminatory capacity for other species of bacteria, such as Borrelia burgdorferi, Francisella tularensis, and the obligate intracellular pathogen Coxiella burnetii (9,10,33). Having identified 10 loci within the A. phagocytophilum HZ strain genome sequence that possessed VNTRs, we examined the extent of heterogeneity at four of these loci among a panel of European A. phagocytophilum strains, thereby obtaining preliminary evidence for the usefulness of MLVA as a sensitive tool for discrimination of the species.…”
mentioning
confidence: 99%